PONCE DE LEÓN ELIZONDO, Ana (Coord.); ALONSO RUIZ, Rosa Ana; FRAILE ARANDA, Antonio; VALDEMOROS SAN EMETERIO, M.ª Ángeles y PALOMERO PESCADOR, José Emilio (2009): La educación motriz para niños de 0 a 6 años. Madrid: Biblioteca Nueva, 238 páginas, ISBN 978-84-9742-968-9. - Rafael Ramos Echazarreta (Universidad de La Rioja, 2013)
PONCE DE LEÓN ELIZONDO, Ana (Coord.); ALONSO RUIZ, Rosa Ana; FRAILE ARANDA, Antonio; VALDEMOROS SAN EMETERIO, M.ª Ángeles y PALOMERO PESCADOR, José Emilio (2009): La educación motriz para niños de 0 a 6 años. Madrid: Biblioteca Nueva, 238 páginas, ISBN 978-84-9742-968-9.